Tukar Guling (Ruislag) Tanah Wakaf dalam Perspektif Hukum Positif dan Hukum Islam di Indonesia - Imroatus Sholicha (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
This study aims to analyze the mechanism of waqf land exchange (ruislag) from the perspectives of Indonesian positive law and Islamic law, as well as to examine the synchronization between the two legal systems in contemporary waqf management practices. This issue has become increasingly relevant in line with the acceleration of infrastructure development, which frequently intersects with waqf assets, particularly waqf land located in strategic areas. This research employs a qualitative approach using a library research method. Data were collected through a systematic review of statutory regulations, classical and contemporary fiqh literature, peer-reviewed journal articles, and relevant official documents. The data were analyzed using a descriptive-analytical approach with an emphasis on comparing positive legal norms and the views of Islamic legal schools concerning the concept of waqf substitution (istibdal). The findings indicate that Indonesian positive law regulates waqf land exchange in a strict and exceptional manner, emphasizing public interest, equivalence or superiority in the value and benefits of replacement assets, and state supervision mechanisms. From the perspective of Islamic law, although differences exist among Islamic legal schools, istibdal is generally permissible insofar as it aims to preserve public interest and ensure the sustainability of waqf benefits. These findings demonstrate a substantive convergence between Islamic law and positive law in the practice of waqf land exchange. This study contributes to strengthening equitable and sustainable waqf governance and recommends enhancing transparency and supervision in the implementation of waqf land exchange in Indonesia.